2012
DOI: 10.1101/lm.025213.111
|View full text |Cite
|
Sign up to set email alerts
|

Role of the dorsal hippocampus in object memory load

Abstract: The dorsal hippocampus is crucial for mammalian spatial memory, but its exact role in item memory is still hotly debated. Recent evidence in humans suggested that the hippocampus might be selectively involved in item short-term memory to deal with an increasing memory load. In this study, we sought to test this hypothesis. To this aim we developed a novel behavioral procedure to study object memory load in mice by progressively increasing the stimulus set size in the spontaneous object recognition task. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
73
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(90 citation statements)
references
References 40 publications
(79 reference statements)
9
73
0
Order By: Relevance
“…The hippocampus is critical for the formation of fear conditioning memories [26,27] and nonspatial object memory [28,29]. Furthermore, recent studies indicate the importance of NR2B-containing NMDA receptors in the hippocampus for contextual discrimination [30] and object recognition [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…The hippocampus is critical for the formation of fear conditioning memories [26,27] and nonspatial object memory [28,29]. Furthermore, recent studies indicate the importance of NR2B-containing NMDA receptors in the hippocampus for contextual discrimination [30] and object recognition [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, δGABA A receptors in the hippocampus may substantially contribute to the THIP effects. The hippocampus can modify recognition memory when a novel and/or complex testing environment is used (Oliveira et al, 2010; Sannino et al, 2012) or when the interval between the training and testing phases is short (Rose et al, 2012). The current experiments utilized a complex testing environment that included multiple visual cues and three objects.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicate that the perirhinal cortex rather than the hippocampus is critical for the consolidation of object identities (Brown and Aggleton 2001;Winters and Bussey 2005;Oliveira et al 2010), while others suggest that the hippocampus is critical for this process (Cohen et al 2013). Recent work addressed this issue and revealed that when the number of objects in the task was increased (thus making the task more difficult) it became more and more dependent on the hippocampus (Sannino et al 2012). Because sleep deprivation also impairs memory consolidation of object identity using a simple version of the task that does not require the hippocampus, other regions such as the perirhinal cortex may also be susceptible to sleep loss (Halassa et al 2009;Oliveira et al 2010).…”
Section: Sleep and Fear Memoriesmentioning
confidence: 96%